Pengaruh BOPO, NIM Serta ROA Terhadap CAR Pada Bank Swasta Nasional Devisa Yang Tercatat Di BEI - Medika Julia Jonardy; Nanu Hasanuh (LPPM POLITEKNIK LP3I BANDUNG, 2022)
This study aims to determine and analyze the impact of managing operating costs, managing productive assets, and considering the ability of assets to generate profits on the risk of loss that may be faced by the company. The sample used in this study is a national private foreign exchange bank listed on the Indonesia Stock Exchange for the 2015-2020 period. To conduct this research, a sample of 36 data is needed. This study uses several methods, namely classical assumption testing, hypothesis testing, and multiple regression analysis. Meanwhile, to help the calculations in this study used statistical methods from the SPSS program. This study finds out whether the BOPO and ROA variables have no effect on the CAR variable, while the NIM variable has an effect on the CAR. With this study it can be concluded that the company must pay attention to and regulate capital adequacy properly so that the health of the bank is always well maintained.